Species-Specific Differences in Sperm Chromatin Decondensation Between Eutherian Mammals Underlie Distinct Lysis Requirements - Ribas-Maynou, Jordi; Garcia-Bonavila, Estela; Hidalgo, Carlos O.; Catalán, Jaime; Miró, Jordi; Yeste, Marc (Frontiers in Cell and Developmental Biology, 2021)
Sperm present a highly particular DNA condensation that is acquired during their differentiation. Protamines are key elements for DNA condensation. However, whereas the presence of protamine 1 (P1) is conserved across mammalian species, that of protamine 2 (P2) has evolved differentially, only existing a few species that use both protamines for sperm DNA condensation. In addition, altered proportions of P1/P2 and alterations in the expression of P1 have previously been associated to infertility and DNA damage disorders. On the other hand, different methods evaluating DNA integrity, such as Sperm Chromatin Dispersion (SCD) and Comet tests, need a previous DNA decondensation. Related with this, the present study aims to analyze the resilience of sperm DNA to decodensation in different mammalian species. Sperm samples from humans, horses, cattle, pigs and donkeys were used. Samples were embedded in low melting point agarose and treated with lysis solutions to induce DNA decondensation and formation of sperm haloes. The treatment consisted of three steps: 1) SDS+DTT incubation for 30 min; 2) DTT+NaCl treatment for 30 min; and 3) DTT+NaCl+Proteinase K treatment with a variable time of 0, 30 or 180 min. How incubation with proteinase K for 0, 30 and 180 min affected DNA decondensation was tested through analyzing core and halo diameters in 50 sperm per sample. Halo/core length ratio was used as an indicator of chromatin decondensation. While incubation time with proteinase K had no impact on halo/core length ratios in species having P1 and P2 (human, equine and donkey), DNA decondensation of pig and cattle sperm, which only present P1, significantly (P<0.05) increased following incubation with proteinase K for 180 min. In conclusion, longer incubations in lysis treatment with proteinase K lead to higher DNA decondensation in porcine and bovine sperm. This suggests that tests intended to analyze DNA damage, such as halo or Comet assays, require complete chromatin deprotamination to achieve higher sensitivity in DNA break detection.